The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0095244319900360
|View full text |Cite
|
Sign up to set email alerts
|

Deproteinized natural rubber film reinforced with silane-modified silica nanoparticles

Abstract: Mechanical properties and morphology of the deproteinized natural rubber (NR) films reinforced with modified silica (SiO2) nanoparticles were studied in this research. In the step of deproteinization, a chemical method followed by centrifugation was used to reduce the amount of protein from 0.42 wt% to 0.11 wt%. Structure-modified nanosilica with Silane A174 was used as an additive to reinforce the deproteinized films. The addition of 1 phr of the modified nanosilica exhibited better tensile strength, tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…SMS nanoparticles were prepared from silica nanoparticles and Silane A174 (Sigma-Aldrich Co., Ltd.) and characterized as reported in our previous work [18]. The scanning electron micrographs of SMS nanoparticle cluster are depicted in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SMS nanoparticles were prepared from silica nanoparticles and Silane A174 (Sigma-Aldrich Co., Ltd.) and characterized as reported in our previous work [18]. The scanning electron micrographs of SMS nanoparticle cluster are depicted in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Silica commonly shows hydrophilic property. As in our previous work [18], the polarity of silica nanoparticles was reduced by the introduction of 3-methacryloxypropyltrimethoxy silane onto the silica surface to obtain the fillers having both polar and non polar properties which is similar to that of ENR. Therefore, the present work aims to prepare ENR/silane-modified silica (SMS) nanocomposites by firstly modifying the NR to ENR via epoxidation, then incorporating the SMS into the ENR latex.…”
Section: Introductionmentioning
confidence: 99%
“…44,45 We choose to use silane A174 to alter the character of silica nanoparticles under pH 3.5−4.5. 46 This is due to the chemical bonding or physical adsorption of the hydrolysis groups of silane A174 with the hydroxyl groups on the surface of the particles, forming an organic adsorption layer on the surface of the particles, which enables the modified silica nanoparticles to be well dispersed in the matrix. It also introduces more silicon into the hydrogel, avoids the agglomeration of silica nanoparticles, and retains some of the hydroxyl groups to maintain the hydrophilicity of the silica nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although NR has outstanding mechanical properties, it is known to contain residual allergenic proteins in latex. Previous studies have shown that various treatments can remove rubber proteins from latex, particularly those on the rubber particles, e.g., enzymatic deproteinization, surfactant washing, saponification, and urea treatments [ 6 , 7 , 8 , 9 , 10 , 11 ]. Protein removal by urea is an ideal method for industrial applications as it is simple, can be performed at ambient temperature and takes a shorter time than enzymatic treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%